SGS-LTER standard met data: Cr21x station 12 - meteorological data on the Central Plains Experimental Range in Nunn, Colorado, USA 1986-2010, ARS study number 4 - Parton, William (Colorado State University. Libraries, 1986)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. The objective of this study is to collect baseline meteorological data for the CPER. Datasets auto12_climdb and man11_climdb have been processed for quality and missing values.
The Short Grass Steppe site encompasses a large portion of the Colorado Piedmont Section of the western Great Plains. The extent is defined as the boundaries of the Central Plains Experimental Range (CPER). The CPER has a single ownership and landuse (livestock grazing). The PNG is characterized by a mosaic of ownership and land use. Ownership includes federal, state or private and land use consists of livestock grazing or row-crops. There are NGO conservation groups that exert influence over the area, particularly on federal lands.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: temperature; wind; radiation; evaporation; cloud cover; precipitation; water; climate; inorganic nutrients; weather; meteorology